Experimental study of method of determination the level of critical information infrastructure importance in the civil aviation - Сидоренко, Вікторія Миколаївна; Гнатюк, Сергій Олександрович; Юдін, Олексій Юрійович (Ukrainian Information Security Research Journal, 2017)
In recent times all over the world the number of different emergency situations was increased. Every day mass media informs about natural and man-caused disasters, weapon conflicts, acts of terrorism, global crimes, acts of piracy that were committed by both crime organizations and single offenders. Increasingly frequently as a result of these events many people falls a victim and also state critical importance systems and resources can be damaged. By this means most of world leader states have attended to methods and means of identifying, systematization and security assurance for critical infrastructure objects. Loss or operational breakdown of these objects can cause significant or irreparably damage for national security of the state. For adequacy security methods implementation it`s very important to determine the importance (criticality) level of state information infrastructure objects in some sector. In view of this the method of determination the level of the critical information infrastructure importance in the civil aviation was proposed and it gives a possibility to assess the importance level and rank critical aviation information systems both by both quantitative and qualitative parameters. Follow-up study contains proposed experimental technique and with help of this method adequacy was checked. It confirms ability to determine the importance level of different critical aviation information systems: information systems of air navigation service, aircraft board information systems, information systems of air companies and airports.